Quantum processes, systems, and information - Schumacher, Benjamin; Westmoreland, Michael D. (Cambridge ; New York : Cambridge University Press, 2010)
"A new and exciting approach to the basics of quantum theory, this u ndergraduate textbook contains extensive discussions of conceptual puzz les and over 800 exercises and problems. Beginning with three elementar y 'qubit' systems, the book develops the formalism of quantum theory, a ddresses questions of measurement and distinguishability, and explores the dynamics of quantum systems. In addition to the standard topics cov ered in other textbooks, it also covers communication and measurement, quantum entanglement, entropy and thermodynamics, and quantum informati on processing. This textbook gives a broad view of quantum theory by em phasizing dynamical evolution, and exploring conceptual and foundationa l issues. It focuses on contemporary topics, including measurement, tim e evolution, open systems, quantum entanglement, and the role of inform ation"--Provided by publisher.
"This textbook gives a broad view of quantum theory by emphasizing d ynamical evolution, and exploring conceptual and foundational issues. I t focuses on contemporary topics, including measurement, time evolution , open systems, quantum entanglement, and the role of information"--Pro vided by publisher.
1. Bits and quanta -- 2. Qubits -- 3. States and observables -- 4. D istinguishability and information -- 5. Quantum dynamics -- 6. Entangle ment -- 7. Information and ebits -- 8. Density operators -- 9. Open sys tems -- 10. A particle in space -- 11. Dynamics of a free particle -- 1 2. Spin and rotation -- 13. Ladder systems -- 14. Many particles -- 15. Stationary states in 1-D -- 16. Bound states in 3-D -- 17. Perturbatio n theory -- 18. Quantum information processing -- 19. Classical and qua ntum entropy -- 20. Error correction -- Appendixes - Index.
Includes index.
Keywords: Quantum theory -- Textbooks